IMPLEMENTASI SUPERVISI AKADEMIK DI SMP - Erlina Indrawati; Manap Somantri; Osa Juarsa (UNIVERSITAS BENGKULU, 2017)
The purpose of this study are to describe about academic supervision program, the implementation of academic supervision, the evaluation through the process and result of academic supervision and the headmaster followed action in implementing the academic supervision in Junior High School 13 South Bengkulu. This study used a qualitative approach. Data was collected through interviews, observation and documentation. After the research we can conclude that the implementation of academic supervision had been done fit to common academic supervision principle. The continued action that is taken by the headmaster in implementing academic supervision were by re-observe the result of supervision, made some revision toward supervision program, and made some improvement to the teachers individually or group .